Study on the morphological development and cellular ultrastructure of early stage of differentiation of floral bud in tuber mustard (Brassica juncea Coss. var tumida Tsen et Lee) - CHEN Zhu-jun; CHEN Di-feng; WANG Bing-liang; Chen Xue-jun (浙江大学学报. 农业与生命科学版)
Based on the morphological characteristics of vegetative cone in stem apex at the end of two-leaf-stage seedlings of tuber mustard which was observed by optical microscope and transmission electron microscope, during the 288 h continuous light treatment, the process of early stage of floral bud differentiation was divided into 5 stages: Non-differentiation stage which the seedlings was uninduced by light; The would-be differentiating stage of floral primodium, after 72 h light treatment which the second leaf was fully expanded; The initial differentiation stage, after 144 h treatment when the third leaf was fully expanded; The elongating and expanding stage after 216 h treatment when the forth leaf was fully expanded; The sepal forming stage, after 288 h treatment when the fifth leaf was fully expanded. The development of floral bud in early mature variety was earlier than late ones. The significant changes were obseved in the morphology, size, number and the degree of development of nuclei, nucleole, mitochondrial and chloroplast of apicalmeristem cell. There were two or more nucleole in the nuclei of the apicalmeristem cell when the plant went into reproductive phase from vegetative phase.